HUBUNGAN KUALITAS TIDUR DENGAN NYERI KEPALA MIGRAIN DAN TENSION TYPE HEADACHE PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA ANGKATAN 2019 - TRIA ARDITA; SAID MUNAZAR RAHMAT; NANDA SARI NURALITA (LP2MTBM MAKARIOZ, 2023)
Headache is an uncomfortable sensation felt in the head area due to anything that damages or has the potential to cause structural damage. Headache includes two namely primary and secondary. Primary headaches are the most common headaches worldwide. One of the causes or risk factors for headaches is sleep disorders. Sleep disturbances need to be considered as one of the main triggers for headaches. To determine the relationship between sleep quality and migraine headaches and tension-type headaches. This type of research is an analytic study with a cross-sectional design where data collection is only taken once to determine the relationship between sleep quality and migraine headache and tension-type headache. The samples used in this study amounted to 67 samples. Where the sample is found in students of the medical faculty of the Muhammadiyah University of North Sumatra, class of 2019. Collecting data by filling out a questionnaire. Then the data collection technique was simple random sampling with the Chi-square test. This study showed that there was a significant relationship between poor sleep quality and migraine headaches and tension-type headaches in students of the Faculty of Medicine, Muhammadiyah University, North Sumatra, class of 2019 as evidenced by the P value = 0,023 which is smaller than P < 0,05. Based on the results of this study, it can be concluded that there is a relationship between sleep quality and migraine headaches and tension-type headaches.